EDUKASI VAKSIN COVID 19 PADA LANSIA DI KELURAHAN POLEWALI TANETE RIATTANG BARAT: EDUKASI VAKSIN COVID 19 PADA LANSIA DI KELURAHAN POLEWALI TANETE RIATTANG BARAT - Nursyahraeni Madika Rahman; Sitti Asiah Yakub; Andi Amin Nur; Rezki Rezki (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2023)
The increasing number of elderly people is accompanied by problems faced by the elderly, one of which is Covid-19. The elderly are a group that is very vulnerable to exposure to Covid-19 and therefore requires services from various parties, including the government. Efforts that can be made to improve the welfare and health of the elderly are vaccination as a means of preventing transmission of the Covid-19 virus. However, the fact is that not all elderly people accept and are willing to be vaccinated against Covid-19, with various problems including a lack of understanding regarding the benefits of the Covid-19 vaccine. So it is very necessary to increase understanding among the elderly about the benefits of vaccination. The focus of this activity is COVID-19 vaccination education for the elderly in Polewali Tanete Riattang Barat Subdistrict which aims to increase the knowledge of the elderly. With activity methods, namely surveys and initial observations and health education regarding the Covid 19 vaccine. The results show that the education about the Covid-19 vaccine carried out in this service activity is very useful in increasing the knowledge of the elderly. In Polewali Tanete Riattang Barat Subdistrict, the success of this activity can also be seen from the enthusiasm of the local government and the response of the elderly